2023
DOI: 10.1038/s41598-023-50517-2
|View full text |Cite
|
Sign up to set email alerts
|

An observational multi-center study on type 2 diabetes treatment prescribing pattern and patient adherence to treatment

Muhammad Daoud Butt,
Siew Chin Ong,
Azra Rafiq
et al.

Abstract: In 2021, the International Diabetes Federation (IDF) reported that the prevalence of diabetes in Pakistan was 9.6%, higher than the global average. However, adherence to treatment guidelines, e.g., American Diabetes Association and Pakistan Endocrine Society and prescription patterns for Oral anti-diabetes (OAD), is poorly understood in Pakistan. Therefore, this study aimed to examine the prescribing practices of anti-diabetic medications, an association of lifestyle modification with drugs prescribed, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, a significant male preponderance (65.0%) was identified, highlighting possible gender-specific consequences in diabetes. Interestingly, other research, such as those by Abdi et al and Upadhyay et al, also found a relative male predominance, while investigations in Nepal and Chennai found a relative female preponderance [ 7 - 10 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, a significant male preponderance (65.0%) was identified, highlighting possible gender-specific consequences in diabetes. Interestingly, other research, such as those by Abdi et al and Upadhyay et al, also found a relative male predominance, while investigations in Nepal and Chennai found a relative female preponderance [ 7 - 10 ].…”
Section: Discussionmentioning
confidence: 95%
“…These results highlight the need of implementing comprehensive management regimens that treat both diabetes and related diseases. Butt et al, Patel et al, and Pitale et al provide further insights into gender distribution, educational levels, family history, and diabetes duration [ 10 , 16 , 17 ]. These studies help to broaden the knowledge of the demographic and clinical aspects of diabetes populations in various countries.…”
Section: Discussionmentioning
confidence: 99%